Determination of the potential antioxidant activity of isolated piperine from white pepper using DPPH, ABTS, and FRAP methods - Akhmad Kharis Nugroho; Nindya - Kusumorini; Suwijiyo - Pramono; Ronny - Martien (Majalah Farmaseutik, 2022)
White pepper (Piper nigrum L) is a native plant of Indonesia that has been used for generations as a spice and traditional medicine. White pepper contains the main alkaloid compound, namely piperine which has antioxidant activity as shown in the previous studies. The purpose of this study was to determine the potential antioxidant activity of isolated piperine compared with n-hexane extract of white pepper using DPPH, ABTS, and FRAP test methods. The isolated piperine was obtained from extraction using Soxhlet with n-hexane as a solvent, followed by purification with cyclohexane. The evaluation of antioxidant activity was carried out using the DPPH method to see free radicals, while the ABTS and FRAP methods evaluated antioxidant activity. Antioxidant activity was expressed as IC50 value and Trolox compound was used as a positive control of antioxidant activity. The analysis results show isolated piperine had antioxidant activity in the ABTS test with the results of 4.35 ± 0.004 mg/mL and 2.53 ± 0.08 mg/mL, respectively  and FRAP test was 10.53 mol TE/g sample and 6.86 mol TE/g sample, respectively. Isolated piperine and n-hexane extract of white pepper did not show their activity as free radical scavengers. The antioxidant activity of isolated piperine was lower than that of n-hexane extract of white pepper. The presence of other compounds in white pepper shows a synergistic interaction in increasing the antioxidant activity of white pepper extract.